2022
DOI: 10.1051/mbcb/2021044
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastomas vs recurrent ameloblastomas: a systematic review

Abstract: Introduction: Ameloblastoma is an odontogenic tumour with high recurrence rate. The objective of the present study was to evaluate existing literature regarding clinical, radiographic, histopathologic features, treatment, and recurrence rate of ameloblastomas and compare it with features of recurrent ameloblastomas. Materials and methods: A systematic review was done based on the PRISMA statement. Search was performed in “Pubmed” database with search terminology “recurrent ameloblastoma”, “ameloblastoma recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…2 It has also been reported that tumours located in the mandible have a higher recurrence rate than those in the maxilla and younger patients have a higher risk of recurrence than older patients. 18 We found significantly higher odds of mandibular lesion being BRAFv600e+, and it has been reported that a significantly higher recurrence of ameloblastoma is seen in mandible. 25,26 Thus it may appear that the higher recurrence in mandibular lesions could be related to BRAFv600e+ status, however, our analysis did not reveal any significant difference in recurrence between the two groups, even after taking jaw site as a covariate.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…2 It has also been reported that tumours located in the mandible have a higher recurrence rate than those in the maxilla and younger patients have a higher risk of recurrence than older patients. 18 We found significantly higher odds of mandibular lesion being BRAFv600e+, and it has been reported that a significantly higher recurrence of ameloblastoma is seen in mandible. 25,26 Thus it may appear that the higher recurrence in mandibular lesions could be related to BRAFv600e+ status, however, our analysis did not reveal any significant difference in recurrence between the two groups, even after taking jaw site as a covariate.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, results of the current study should be interpreted with caution since we were unable to extract those data due to either unreported information or the heterogeneity in the included studies' presentation methods. Nevertheless, the potential for recurrence in ameloblastoma is multifactorial and unlikely to be dependent on BRAF mutational status alone as reported in this recent meta‐analysis of primary versus recurrent ameloblastoma 18 . In this context, it should be noted that the recently recognised adenoid ameloblastoma lacks BRAF mutation despite demonstrating a more aggressive clinical behaviour and up to 45% recurrence compared to conventional ameloblastoma 19–22 .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…4 However, a male predominance has been described by other authors. [18][19][20] This difference could be explained by a large number of cemento-osseous dysplasia cases, often seen and encountered in melanodermal adult women. 21 These tumors can be found at any age with a peak in young adults.…”
Section: Discussionmentioning
confidence: 99%